PENGARUH IKLIM ORGANISASI, PUNISHMENT DAN REWARD TERHADAP KEPUASAN KERJA KARYAWAN DIVISI OPERASI 2 PT SEMEN BATURAJA (PERSERO) TBK - Muhamad Irsan; Luis Marnisah; Fakhry Zamzam (Program Magister Manajemen Indo Global Mandiri University, 2020)
PT Semen Baturaja (Persero) Tbk, as a national cement industry in the struggle for supply and competition with local cement producers remains optimistic to continue marketing their products. Baturaja cement production processes carried out in the directorate of production and development continue to run at the cement plant. One of the operations division 2's role is placed directly under the production and development directorate of PT Semen Baturaja (Persero) Tbk, carrying out strategic tasks in coordinating, directing, and carrying out factory 2 operational activities ranging from raw materials to packaging. Phenomena related to work in the operating division 2 such as the existence of a physical work environment, assessment of penalties and rewards with differences of opinion about differences in work differences between operating and non-operating work can cause differences in job satisfaction of the company. This thesis research uses the verification survey method, aimed at discussing hypotheses and describing variables. Quantitative samples through field data and information directly from the sample. This research is an associative study, where in this study there are related variables and can affect other variables. PT Semen Baturaja (Persero) Tbk, with a significance level of 0,000 <0.05 and t arithmetic 5.203> t table 2.003 and regression regression 0.413. PT Semen Baturaja (Persero) Tbk, with a significance level of 0.465 <0.05 and t -0.715> t table 2.003 and a regression of -0.052, and an appreciation of the work satisfaction of Operational Division 2 employees of PT Semen Baturaja (Persero) Tbk, with a level of significance of 0.00 <0.05 and t arithmetic 7.697> t table 2.003 and a regression of 0.594, which means organization, punishment and gifts together to support positive and significant for employee job satisfaction of Operations Division 2 PT Semen Baturaja (Persero) Tbk with F count 53,411> F table 4,893. Thus this research has successfully completed the theory empirically in the field, it can be concluded about the organizational contribution, punishment and appreciation of the positive and significant impact on job satisfaction of employees of Operations Division 2 of PT Semen Baturaja (Persero) Tbk.